Limited Effect Principle of a Relativistic System - The Calculation Results within a Relativity System Cannot be Applied to the Real World Outside the System (London Journal of Research In Science: Natural and Formal, 2025)
We pointed out 3 general concerns and 12 problems in Einsteins theory of special relativity in [1-4], which got positive feedback. Here we present a newly derived Limited Effect Principle of a Relativistic System. This research followed our method of analyzing mathematical models from the perspective of reviewing the rationality of physical models first, and used this method to derive the Limited Effect Principle of a Relativistic System. This Limited Effect Principle gives obvious evidence that the theory of relativity is misunderstanding the mathematical world from the physical world, which gives us further confidence that the theory of relativity should no longer lead the scientific and technological thinking of mankind.
Keywords: relativity.; Special Theory of Relativity; Einstein; reference body.